(untitled) (Revista Cocar, 2012)
Meu objetivo neste artigo é discutir as idéias sobre educação e pedagogia em dois autores que as trataram com ênfase diferente em suas obras e em suas carreiras acadêmicas. Castoriadis, filósofo, psicanalista, sociólogo, foi um militante do seu projeto de autonomia. Suas idéias sobre a autonomia o aproximam de um outro filósofo, Paulo Freire, que pode ser definido com uma única palavra: educador. As idéias centrais de Freire estão a serviço de sua visão de educação libertadora do sujeito, do mesmo modo como Castoriadis propõe a eliminação da desigualdade social e política através da defesa intransigente da autonomia como a junção da liberdade e da igualdade. A preparação de uma sociedade autônoma deve ser a tarefa de um projeto político de educação que contemple a discussão da "fabricação social" de sujeitos capazes de "propor e discutir a sua lei" e de pensar os limites de sua própria vida social e política. Palavras-Chave: Autonomia. Educação. Imaginário Social. Education as a political project: autonomy lessons in Castoriadis and Freire My objective in this article is to discuss the ideas on education and pedagogy in two authors who have treated them with different emphasis in their works and in their academic careers. Castoriadis, philosopher, psychoanalyst, sociologist, was a militant of his project on autonomy. His ideas on autonomy approximate him of another philosopher, Paulo Freire, who can be defined by a unique word: educator. The central ideas of Freire are serving his vision of education as liberation of the individual, in the same way as Castoriadis proposes the elimination of the social and political inequality through the uncompromising defense of the autonomy as the union of freedom and equality. The preparation of an autonomous society should be the task of a political project of education that contemplates the discussion of the "social production" of individuals capable to "propose and to discuss his/her law" and to think the limits of his/her own social and political life. Keywords: Autonomy. Education. Social Imaginary "